Does Spironolactone Have a Dose-Dependent Effect on Left Ventricular Remodeling in Patients with Preserved Left Ventricular Function After an Acute Myocardial Infarction? - BACAKSIZ, AHMET; Vatankulu, Mehmet Akif; BACAKSIZ, AHMET; Sonmez, Osman; Alihanoglu, Yusuf; KOÇ, FATİH; DEMİR, KENAN; Gul, Enes Elvin; Turfan, Murat; Tasal, Abdurrahman; Kayrak, Mehmet; Yazici, Mehmet; et al. (My University, 2013)
Aims The aim of this study was to investigate the effects of spironolactone on left ventricular (LV) remodeling in patients with preserved LV function following acute myocardial infarction (AMI).
Keywords: acute myocardial infarction